The role of total quality management in improving the organization's performance in light of the Kingdom's 2030 vision: An applied study on the municipality of Heli - Al-Nashiri, Khalil Maqbool Muhammad; Al-Shareef, Talal Muslat Abdullah (Journal of Economic, Administrative and Legal Sciences, 2022)
TQM (Total Quality Management) is a management philosophy that takes the form of a comprehensive management approach or system, which is based on doing radical positive changes that include improving the level of performance within the organization. In the context of the efforts of various organizations within the Kingdom to keep pace with the transformation of the Kingdom’s Vision 2030, this research study comes with the aim of identifying the role of total quality management in improving the organization’s performance in light of the Kingdom’s Vision 2030, This was done through an applied study on the municipality of Heli, which is affiliated with the Municipality of Jeddah in the city of Al-Qunfudah, in the Makkah region. The research used the descriptive analytical method in conducting this study, where the questionnaire was used in collecting primary data from the study population, which consisted of employees working in the municipality of Heli, and the study sample amounted to (20) employees, and the data was analyzed using the (SPSS V22) program. Several results have been reached, most notably: the presence of a large approval rate among the members of the study sample regarding the degree of availability of the requirements for the application of total quality management in the municipality of Heli With a relative weight of (75.2%), The research also found that there are medium degree obstacles facing the application of total quality management in the municipality of Heli from the point of view of the study sample members With a relative weight of (59.4%). The research suggested a number of recommendations, the most important of which are: The necessity of working to involve the workers within the Heli municipality leadership in the decision-making process with the leadership. And interest in the existence of a clear organizational structure for the application of total quality management within the municipality of Helli.
Keywords: Quality; Total Quality Management; Strategic Transformation; Vision 2030